Predictability of positive relationship through personal empowerment - Abu Bakar, Aisyah; Mohamed Osman, Mariana; Abdullah, Muhammad Faris (Malaysian Institute Of Planners, 2019)
Designers have long adopted the knowledge from the field of psychology to expand architectural space’s emotional impacts. Appropriate design strategies can improve and sustain well-being through instilling the sense of empowerment, leading to positive relationships among space occupants. Issue: A large body of the literature has sought to provide a conclusive empirical assessment on the predictability of attitudes and behaviours in positive relationships (PR) through personal empowerment (PE). Purpose: This paper intends to determine the predictability of PR based on PE. Approach: Multiple Correlation and Multiple Linear Regression were conducted to estimate linear associations and parameters of linear equations to predict PR components based on PE items. Findings: Components of PR were predictable by the majority of the PE items and ‘monitoring behaviours to suit with situation’ was the strongest predictor of PR.